Green, Sustainable Architectural Bamboo with High Light Transmission and Excellent Electromagnetic Shielding as a Candidate for Energy-Saving Buildings - Wang, Jing; Wu, Xinyu; Wang, Yajing; Zhao, Weiying; Zhao, Yue; Zhou, Ming; Wu, Yan; Ji, Guangbin (Nano-Micro Letters, 2022)
Currently, light-transmitting, energy-saving, and electromagnetic shielding materials are essential for reducing indoor energy consumption and improving the electromagnetic environment. Here, we developed a cellulose composite with excellent optical transmittance that retained the natural shape and fiber structure of bamboo. The modified whole bamboo possessed an impressive optical transmittance of approximately 60% at 6.23 mm, illuminance of 1000 luminance (lux), water absorption stability (mass change rate less than 4%), longitudinal tensile strength (46.40 MPa), and surface properties (80.2 HD). These were attributed to not only the retention of the natural circular hollow structure of the bamboo rod on the macro, but also the complete bamboo fiber skeleton template impregnated with UV resin on the micro. Moreover, a multilayered device consisting of translucent whole bamboo, transparent bamboo sheets, and electromagnetic shielding film exhibited remarkable heat insulation and heat preservation performance as well as an electromagnetic shielding performance of 46.3 dB. The impressive optical transmittance, mechanical properties, thermal performance, and electromagnetic shielding abilities combined with the renewable and sustainable nature, as well as the fast and efficient manufacturing process, make this bamboo composite material suitable for effective application in transparent, energy-saving, and electromagnetic shielding buildings. Highlights: 1 The whole bamboo mere made directly into cellulose composites, which greatly reduced massive energy consumption from the mechanical pre-processing process. 2 The wall thickness of transparent whole bamboo can reach 6.23 mm. 3 The modified whole bamboo possesses excellent optical transmittance of about 60% at 6.23 mm, the illuminance of 1000 luminance (lux), water absorption stability (the mass change rate less than 4%), longitudinal tensile strength (46.40 MPa), and surface properties (80.2 HD). 4 The combination of excellent transmittance, mechanical properties, surface properties, thermal performance, and electromagnetic shielding properties makes this composite attractive in areas such as transparent, energy-saving, and electromagnetic shielding buildings.